Copper-doped iron sulfide as well as preparation method and application thereof

By preparing copper-doped iron sulfide, the problems of weak mercury demercury performance and low mercury adsorption capacity are solved, and efficient mercury adsorption and economical demercury effects are achieved.

CN119591162AActive Publication Date: 2025-03-11CENT SOUTH UNIV

Patent Information

Application Number
CN202411716661.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

In the prior art, iron sulfide has weak mercury demercury performance and low mercury adsorption capacity, making it difficult to effectively remove mercury in the flue gas.

Method used

Copper-doped iron sulfide is prepared by configuring iron nitrate and copper nitrate into a metal salt solution, adding sulfur source and heating under high pressure conditions to prepare copper-doped iron sulfide.

Benefits of technology

The mercury adsorption capacity of copper-doped iron sulfide is significantly improved, reaching about 9 times that of ordinary iron disulfide. At the same time, the high mercury demercury performance is maintained under a high SO2 atmosphere, which has significant economic advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591162A_ABST
    Figure CN119591162A_ABST
Patent Text Reader

Abstract

The invention provides copper-doped iron sulfide as well as a preparation method and application thereof, and the preparation method of the copper-doped iron sulfide comprises the following steps: S1, preparing a metal salt solution from iron nitrate and copper nitrate; wherein in the metal salt solution, the sum of the molar concentration of iron ions and the molar concentration of copper ions is 0.003 mol / 25 ml to 0.06 mol / 25 ml; s2, dissolving a sulfur source in a metal salt solution to obtain a mixed solution, heating the mixed solution to 120-180 DEG C under a high-pressure condition, carrying out heat preservation for 12 hours, and separating solids in the mixed solution to obtain copper-doped iron sulfide; the molar concentration of the sulfur source in the mixed solution is 0.01-0.1 mol / 50ml; or, the metal salt solution is heated to 120-180 DEG C under the high-pressure condition, heat preservation is conducted for 12 h, a precursor is obtained, the precursor and elemental sulfur are mixed and then heated to 400 DEG C, heat preservation is conducted for 2 h, and the copper-doped iron sulfide is obtained. The adsorption capacity of the ferric sulfide mercury is improved, and meanwhile, the method has a remarkable economic advantage in the aspect of HgO removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy metal control, and in particular relates to copper-doped iron sulfide and a preparation method and application thereof. Background Art

[0002] Metal sulfides have the advantages of strong resistance to SO2 poisoning and are rich in mercury-loving sulfur elements. They are currently the most promising adsorption materials for high-sulfur flue gas demercuration. As the cheapest metal sulfide, iron sulfide has a significant cost advantage over copper sulfide, molybdenum sulfide, etc., but its demercuration performance is far weaker than other metal sulfides. Researchers found that the mercury adsorption capacity of hydrothermally synthesized iron disulfide is only 2.7 mg·g -1 .

[0003] Based on this, it is necessary to provide a copper-doped iron sulfide and a preparation method and application thereof to solve the technical problems existing in the above-mentioned common technologies. Summary of the invention

[0004] In order to solve the technical problems of weak mercury removal performance and low mercury adsorption capacity of iron sulfide in the above-mentioned conventional technologies, the present invention provides a method for preparing copper-doped iron sulfide, comprising the steps of:

[0005] S1. preparing a metal salt solution from ferric nitrate and copper nitrate; wherein the sum of the molar concentrations of iron ions and copper ions in the metal salt solution is 0.003 to 0.06 mol / 25 ml;

[0006] S2. dissolving a sulfur source in a metal salt solution to obtain a mixed solution, heating the mixed solution to 120-180° C. under high pressure for 12 hours, and separating the solid matter therein to obtain copper-doped iron sulfide; the molar concentration of the sulfur source in the mixed solution is 0.01-0.1 mol / 50 ml;

[0007] Alternatively, the metal salt solution is heated to 120-180° C. under high pressure and kept warm for 12 hours to obtain a precursor, and the precursor is mixed with elemental sulfur and heated to 400° C. and kept warm for 2 hours to obtain copper-doped iron sulfide.

[0008] Furthermore, the sulfur source includes thiourea and sodium sulfide.

[0009] Furthermore, when the sulfur source is thiourea, heating the mixed solution to 120-180° C. under high pressure conditions and keeping the temperature for 12 hours includes: heating the mixed solution to 120-140° C. under high pressure conditions and keeping the temperature for 12 hours.

[0010] Furthermore, when the sulfur source is sodium sulfide, heating the mixed solution to 120-180° C. under high pressure conditions and keeping it warm for 12 hours includes: heating the mixed solution to 160-180° C. under high pressure conditions and keeping it warm for 12 hours.

[0011] Furthermore, the mass ratio of the precursor to the elemental sulfur is 1:1-2.

[0012] Furthermore, in the copper-doped iron sulfide, the molar ratio of iron ions to copper ions is 0.9-0.95:0.05-0.1.

[0013] The present invention provides a copper-doped iron sulfide, which is prepared by any one of the above methods for preparing the copper-doped iron sulfide.

[0014] The present invention also provides an application of the copper-doped iron sulfide in flue gas demercuration, comprising the steps of passing mercury-containing flue gas into the copper-doped iron sulfide for demercuration reaction, wherein the reaction temperature of the demercuration reaction is 25°C to 50°C, and the flow rate of the mercury-containing flue gas is 600 mL·min -1 , the mercury-containing flue gas contains Hg 0 Concentration 100~200μg.m -3 .

[0015] Furthermore, the mercury-containing flue gas includes sulfur-containing flue gas, and the volume fraction of sulfur dioxide in the sulfur-containing flue gas is 4-8%, and the volume fraction of oxygen is 4-8%.

[0016] Furthermore, the concentration of HCl in the mercury-containing flue gas is 2 to 6 ppm.

[0017] Compared with the prior art, the present invention has at least the following advantages:

[0018] The present invention provides a method for preparing copper-doped iron sulfide, wherein the copper is uniformly dispersed in the iron sulfide. 3+ , Cu 2+ and S2 2- are the active sites for mercury removal in copper-doped iron sulfide, and they participate in Hg 0 The oxidative adsorption of iron sulfide and its final fixation as HgS, copper doping makes the surface of iron sulfide produce more S2 2- , this part S2 2- It is formed by the coordination of S and Cu. In addition, high-valent Cu is introduced on the surface of copper-doped iron sulfide. 2+ , accounting for 26.61%

[0019] The applicant also found that copper doping reduces the energy gap of FeS2 from 0.647eV to 0.10eV, and the d-band center shifts significantly negatively, promoting Hg0 Adsorption and electron transfer; Compared with the single Fe site and Cu site, the charge density of the Fe-Hg bond and Cu-Hg bond regions increases, which strengthens the charge transfer of Hg atoms and enhances the interaction between Hg and the Fe and Cu sites of copper-doped iron sulfide. The d orbitals of the Fe and Cu sites overlap with the s orbitals of Hg, exerting a synergistic demercuration effect, and the adsorption energy increases from -55.85 kJ·mol -1 (Fe site) and -39.61 kJ·mol -1 (Cu site) increased to -68.70 kJ·mol -1 In addition, the pre-adsorbed Cu sites on the FeS2(100) surface cooperate with the Fe sites to 0 The adsorption energy is -96.52 kJ·mol -1 , Cu site to Hg 0 The adsorption energy is -80.89 kJ·mol -1 .

[0020] Based on the above, copper-doped iron sulfide realizes Hg 0 The adsorption performance is optimized, and its mercury adsorption capacity is significantly improved compared with other metal sulfides, reaching that of ordinary iron disulfide (2.7 mg·g -1 ), while taking into account the advantage of iron sulfide's strong resistance to SO2 poisoning, it can maintain high mercury removal performance in a high sulfur dioxide atmosphere with a SO2 volume fraction of 6%, and is suitable for high SO2 smelting flue gas mercury removal.

[0021] In addition, Fe 0.9 Cu 0.1 SS Hg removal 0 The cost is 471.00 yuan / (kg Hg 0 ) (considering only the raw material cost of adsorbent preparation), it is only 2 / 5 of ordinary iron disulfide and 1 / 250 of carbon-based adsorbent. Therefore, copper doping achieves an increase in the adsorption capacity of iron sulfide mercury, while at the same time 0 It has significant economic advantages in removal and has good application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0023] Figure 1 (a) is a scanning electron micrograph of FeS2-S in Analysis Example 1 of the present invention, Figure 1(b) Fe in the analysis example 1 of the present invention 0.9 Mo 0.1 Scanning electron micrograph of SS, Figure 1 (c) Analysis Example 1Fe of the present invention 0.9 Cu 0.1 Scanning electron micrograph of SS.

[0024] Figure 2 (a) is an X-ray diffraction diagram of iron sulfide before and after metal cation doping in analysis example 1 of the present invention; Figure 2 (b) is the X-ray diffraction pattern of copper-doped iron sulfide with different copper addition amounts in Analysis Example 1 of the present invention.

[0025] Figure 3 The FeS2-S and Fe 0.9 Cu 0.1 Raman spectrum of SS.

[0026] Figure 4 (a) is the Fe 2p orbital X-ray photoelectron spectrum of iron sulfide before and after doping in Analytical Example 1 of the present invention; Figure 4 (b) is the S2p orbital X-ray photoelectron spectrum b of iron sulfide before and after doping in the analysis example 1 of the present invention: Figure 4 (c) is the Mo 3d orbital X-ray photoelectron spectrum of iron sulfide before and after doping in Analytical Example 1 of the present invention; Figure 4 (d) is the Cu 2p orbital X-ray photoelectron spectrum of iron sulfide before and after doping in Analysis Example 1 of the present invention.

[0027] Figure 5 (a) is the Hg content of FeS2 prepared at different sulfurization temperatures using thiourea as the sulfur source in Analysis Example 2 of the present invention at 50°C and 6% SO2+6% O2 0 Adsorption performance; Figure 5 (b) is the Fe prepared at different sulfurization temperatures using thiourea as the sulfur source in Analysis Example 2 of the present invention. 0.9 Cu 0.1 S Hg at 50℃, 6% SO2+6% O2 0 Adsorption performance; Figure 5 (c) is the Fe prepared at different sulfurization temperatures using thiourea as the sulfur source in Analysis Example 2 of the present invention. 0.9 Mo 0.1 S Hg at 50℃, 6% SO2+6% O2 0 Adsorption performance; Figure 5 (d) is the Fe prepared at different sulfidation temperatures using sodium sulfide as the sulfur source in Analysis Example 2 of the present invention. 0.9 Cu 0.1 S Hg at 50℃, 6% SO2+6% O2 0 Adsorption performance.

[0028] Figure 6 The Hg content of the iron sulfide prepared by dry sulfidation in the present invention in Example 3 under 6% SO2+6% O2 is 0 Adsorption performance.

[0029] Figure 7 The Hg content of iron sulfide doped with different copper addition amounts in 6% SO2+6% O2 in the present invention is analyzed in Example 4. 0 Adsorption performance.

[0030] Figure 8 (a) Fe in the analysis example 5 of the present invention 0.9 Cu 0.1 Hg in SS under different flue gas components 0 Adsorption performance; Figure 8 (b) Fe in the analysis example 5 of the present invention 0.9 Cu 0.1 Hg in SS under different flue gas components 0 Adsorption performance.

[0031] Fig. 9 The Fe in the analysis example 6 of the present invention 0.9 Cu 0.1 SS and FeS2-S under 6% SO2+6% O2 and 50℃ 0.9 Cu 0.1 Long-term adsorption curve of SS.

[0032] Fig.10 (a) FeS2-S and Fe in the analysis example 6 of the present invention 0.9 Cu 0.1 SS adsorption of Hg 0 The pseudo-first order and Fig.10 (b) FeS2-S and Fe in the analysis example 6 of the present invention 0.9 Cu 0.1 SS adsorption of Hg 0 Pseudo-second-order kinetic model.

[0033] Fig.11 (a) is the adsorption of Hg in the analysis example 7 of the present invention 0 Front and rear Fe 0.9 Cu 0.1 X-ray photoelectron spectroscopy of SS on Fe 2p orbitals, Fig.11 (b) Hg adsorbed in the analysis example 7 of the present invention 0 Front and rear Fe 0.9 Cu 0.1 X-ray photoelectron spectrum of SS in S2p orbital, Fig.11 (c) Hg adsorbed in the analysis example 7 of the present invention0 Front and rear Fe 0.9 Cu 0.1 X-ray photoelectron spectroscopy of SS on Cu 2p orbitals, Fig.11 (d) is the adsorption of Hg in the analysis example 7 of the present invention 0 Front and rear Fe 0.9 Cu 0.1 X-ray photoelectron spectrum of SS in Hg 4f orbitals.

[0034] Fig.12 The Fe in the analysis example 8 of the present invention 0.9 Cu 0.1 Temperature-programmed mercury desorption curve of SS. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0037] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.

[0038] The present invention provides a method for preparing copper-doped iron sulfide, comprising the steps of:

[0039] S1. Prepare a metal salt solution by mixing ferric nitrate and copper nitrate; wherein the sum of the molar concentrations of iron ions and copper ions in the metal salt solution is 0.003-0.006 mol / 25 ml.

[0040] Exemplarily, the sum of the molar concentrations of iron ions and copper ions is 0.005 mol / 25 ml.

[0041] S2. Wet sulfurization: dissolve a sulfur source in a metal salt solution to obtain a mixed solution, heat the mixed solution to 120-180°C under high pressure for 12 hours, and separate the copper-doped iron sulfide by suction filtration; the molar concentration of the sulfur source in the mixed solution is 0.01-0.1 mol / 50 ml.

[0042] In some embodiments, the sulfur source may be first dissolved in deionized water to form a sulfur source solution with a sulfur source molar concentration of 0.01-0.1 mol / 50 ml, and then the sulfur source solution is mixed with a metal salt solution and stirred for 2-3 hours to obtain a mixed solution.

[0043] In some specific embodiments, the step of heating the mixed solution to 120-180°C under high pressure conditions and keeping it warm for 12 hours, and filtering and separating to obtain copper-doped iron sulfide may include the steps of: transferring the mixed solution into a 100 ml Teflon-lined autoclave, heating it to 120-180°C and keeping it warm for 12 hours, filtering and separating to obtain black powder, and then washing the black powder alternately with deionized water and ethanol for several times, and drying to obtain copper-doped iron sulfide.

[0044] The drying temperature may be 60° C., and the drying time may be 12 h.

[0045] In some embodiments, the molar concentration of the sulfur source in the mixed solution may be 0.01-0.05 mol / 50 ml; in some more specific embodiments, the molar concentration of the sulfur source in the mixed solution may be 0.02 mol / 50 ml.

[0046] In some embodiments, the sulfur source includes thiourea and / or sodium sulfide.

[0047] When the sulfur source is thiourea, heating the mixed solution to 120-180° C. under high pressure and keeping the temperature for 12 hours comprises: heating the mixed solution to 120-140° C. under high pressure and keeping the temperature for 12 hours.

[0048] When the sulfur source is sodium sulfide, the heating the mixed solution to 120-180° C. under high pressure conditions and keeping the temperature for 12 hours includes: heating the mixed solution to 160-180° C. under high pressure conditions and keeping the temperature for 12 hours.

[0049] Or, dry sulfidation: the metal salt solution is heated to 120-180° C. under high pressure conditions and kept warm for 12 hours to obtain a precursor, and the precursor is mixed with elemental sulfur and heated to 400° C. and kept warm for 2 hours to obtain copper-doped iron sulfide.

[0050] In some specific embodiments, the metal salt solution can be transferred into a 100 mL Teflon-lined autoclave, heated to 120-180° C. and kept warm for 12 h, and a reddish-brown precursor is obtained by filtering, washing and drying. The precursor is then mixed evenly with elemental sulfur and sent into a tubular furnace, and then heated to 400° C. under a N2 atmosphere and kept warm for 2 h.

[0051] The mass ratio of the precursor to the elemental sulfur may be 1:1-2; in some embodiments, the mass ratio of the precursor to the elemental sulfur may be 1:1.5.

[0052] In some embodiments, the molar ratio of iron ions to copper ions in the copper-doped iron sulfide is 0.9-0.95:0.05-0.1.

[0053] In some more specific embodiments, the molar ratio of iron ions to copper ions in the copper-doped iron sulfide may be 0.9:0.1.

[0054] When the molar ratio of iron ions to copper ions in the copper-doped iron sulfide is 0.9-0.95:0.05-0.1, the molar ratio of iron nitrate to copper nitrate in the metal salt solution is 0.9-0.95:0.05-0.1.

[0055] When the molar ratio of iron ions to copper ions in the copper-doped iron sulfide is 0.9:0.1, the molar ratio of iron nitrate to copper nitrate in the metal salt solution is 0.9:0.1.

[0056] The present invention provides a copper-doped iron sulfide, which is prepared by any one of the above methods for preparing the copper-doped iron sulfide.

[0057] The present invention provides an application of the copper-doped iron sulfide in flue gas demercuration, comprising the steps of passing mercury-containing flue gas into the copper-doped iron sulfide for demercuration reaction, wherein the reaction temperature of the demercuration reaction is 25°C to 50°C, and the flow rate of the mercury-containing flue gas is 600 mL·min -1 , the mercury-containing flue gas contains Hg 0 Concentration 100~200μg.m -3 .

[0058] For example, the mercury-containing flue gas may be cooled to a temperature of 25 to 50° C., thereby providing a reaction environment of 25 to 50° C. for the mercury removal reaction.

[0059] In some embodiments, Hg in mercury-containing flue gas 0 Concentration 120~180μg.m -3 In some more specific embodiments, Hg 0 Concentration 150 μg.m -3 .

[0060] Furthermore, the mercury-containing flue gas includes sulfur-containing flue gas, and the volume fraction of sulfur dioxide in the sulfur-containing flue gas is 4-8%, and the volume fraction of oxygen is 4-8%.

[0061] In some embodiments, the volume fraction of sulfur dioxide in the sulfur-containing flue gas is 5-7%, and the volume fraction of oxygen is 5-7%. In some specific embodiments, the volume fraction of sulfur dioxide in the sulfur-containing flue gas is 6%, and the volume fraction of oxygen is 6%.

[0062] Furthermore, the concentration of HCl in the mercury-containing flue gas is 2-6 ppm. In some specific embodiments, the concentration of HCl in the mercury-containing flue gas is 5 ppm.

[0063] In order to facilitate those skilled in the art to further understand the present invention, examples are given below:

[0064] Example 1: One-step hydrothermal synthesis of copper-doped iron sulfide using wet sulfidation

[0065] S1. Dissolve a total of 0.005 mol of ferric nitrate and copper nitrate in 25 mL of deionized water to form a metal salt solution;

[0066] S2. Dissolve thiourea (0.02 mol, A) and sodium sulfide (0.02 mol, B) in 25 mL of deionized water to form two sulfur source solutions, stir the sulfur source solution and the metal salt solution for 2 h to form a mixed solution, then transfer the mixed solution into a 100 mL Teflon-lined autoclave, keep it at a certain temperature for 12 h, separate it by suction filtration to obtain a black powder, wash it several times with deionized water and ethanol alternately, and then dry it at 60 ° C for 12 h. The obtained copper-doped iron sulfide is recorded as Fe x Cu (1-x) Syz, where x represents the molar amount of Fe / (Fe+Cu), y represents the sulfur source, and z represents the sulfurization temperature.

[0067] That is, copper-doped iron sulfide with thiourea as the sulfur source is denoted as Fe x Cu (1-x) SA; copper-doped iron sulfide with sodium sulfide as the sulfur source is denoted as Fe x Cu (1-x) SB;

[0068] The molar ratio of ferric nitrate to copper nitrate in the metal salt solution was changed. When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution was 0.95:0.05, Fe 0.95 Cu 0.05 SA or Fe 0.95 Cu 0.05 SB;

[0069] When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution is 0.9:0.1, Fe 0.9 Cu 0.1 SA or Fe 0.9 Cu 0.1 SB;

[0070] When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution is 0.85:0.15, Fe 0.85 Cu 0.15 SA or Fe 0.85 Cu 0.15 SB.

[0071] Example 2 Synthesis of copper-doped iron sulfide by dry sulfidation

[0072] S1. Dissolve 0.005 mol of ferric nitrate and copper nitrate in 25 mL of deionized water to form a metal salt solution;

[0073] S2. The metal salt solution was transferred into a 100 mL Teflon-lined autoclave, heated to 160 °C and kept warm for 12 h. A reddish-brown precursor was obtained by filtration, washing and drying. The precursor was then mixed with elemental sulfur (mass ratio 2:3) and evenly sent into a tube furnace. The mixture was then heated to 400 °C in a N2 atmosphere and kept warm for 2 h. The copper-doped iron sulfide obtained was recorded as Fe x Cu (1-x) SS.

[0074] The molar ratio of ferric nitrate to copper nitrate in the metal salt solution was changed. When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution was 0.95:0.05, Fe 0.95 Cu 0.05 SS;

[0075] When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution is 0.9:0.1, Fe 0.9 Cu 0.1 SS;

[0076] When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution is 0.85:0.15, Fe 0.85 Cu 0.15 SS.

[0077] Comparative Example 1: Synthesis of molybdenum-doped iron sulfide by wet sulfurization

[0078] S1. A total of 0.005 mol of iron nitrate and ammonium molybdate was dissolved in 25 mL of deionized water to form a metal salt solution;

[0079] S2. Dissolve thiourea (0.02 mol, A) and sodium sulfide (0.02 mol, B) in 25 mL of deionized water to form two sulfur source solutions. Stir one of the sulfur source solutions with the metal salt solution for 2 h to form a mixed solution. Then transfer the mixed solution into a 100 mL Teflon-lined autoclave and keep it at a certain temperature for 12 h. Separate and filter to obtain a black powder. Wash it several times with deionized water and ethanol alternately, and then dry it at 60 ° C for 12 h. The obtained copper-doped iron sulfide is recorded as Fe x Mo (1-x) Syz, where x represents the molar amount of Fe / (Fe+Cu), y represents the sulfur source, and z represents the sulfurization temperature.

[0080] That is, molybdenum-doped iron sulfide with thiourea as the sulfur source is denoted as Fe x Mo (1-x) SA; Molybdenum-doped iron sulfide with sodium sulfide as sulfur source is denoted as Fe x Mo (1-x) SB;

[0081] When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution is 0.9:0.1, Fe 0.9 Mo 0.1 SA or Fe 0.9 Mo 0.1 SB.

[0082] Comparative Example 2: Synthesis of molybdenum-doped iron sulfide by dry sulfidation

[0083] S1. Dissolve a total of 0.005 mol of iron nitrate and ammonium molybdate in 25 mL of deionized water to form a metal salt solution;

[0084] S2. The metal salt solution was transferred into a 100 mL Teflon-lined autoclave, heated to 160 °C and kept warm for 12 h. A reddish-brown precursor was obtained by filtration, washing and drying. The precursor was then mixed with elemental sulfur (mass ratio 2:3) and evenly sent into a tube furnace. The mixture was then heated to 400 °C in a N2 atmosphere and kept warm for 2 h. The copper-doped iron sulfide obtained was recorded as Fe x Mo (1-x) SS.

[0085] When the molar ratio of ferric nitrate to copper nitrate in the metal salt solution is 0.9:0.1, Fe 0.9 Mo 0.1 SS.

[0086] Comparative Example 3: Synthesis of copper-doped iron sulfide by wet sulfidation

[0087] S1. Dissolve a total of 0.005 mol of ferric nitrate in 25 mL of deionized water to form a metal salt solution;

[0088] S2. Dissolve thiourea (0.02 mol, A) and sodium sulfide (0.02 mol, B) in 25 mL of deionized water to form two sulfur source solutions, stir the sulfur source solution and the metal salt solution for 2 h to form a mixed solution, then transfer the mixed solution into a 100 mL Teflon-lined autoclave, keep it at a certain temperature for 12 h, separate it by suction filtration to obtain a black powder, wash it several times with deionized water and ethanol alternately, and then dry it at 60 ° C for 12 h. The obtained copper-doped iron sulfide is recorded as Fe x Cu (1-x) Syz, where x represents the molar amount of Fe / (Fe+Cu), y represents the sulfur source, and z represents the sulfurization temperature.

[0089] That is, the iron sulfide with thiourea as the sulfur source is recorded as FeS2-A; the copper-doped iron sulfide with sodium sulfide as the sulfur source is recorded as FeS2-B;

[0090] Comparative Example 4: Synthesis of Iron Sulfide by Dry Sulfidation

[0091] S1. Dissolve a total of 0.005 mol of ferric nitrate in 25 mL of deionized water to form a metal salt solution;

[0092] S2. The metal salt solution was transferred into a 100 mL Teflon-lined autoclave, heated to 160 °C and kept warm for 12 h. A reddish-brown precursor was obtained by filtering, washing and drying. The precursor was then mixed evenly with elemental sulfur (mass ratio 2:3) and sent into a tubular furnace. The mixture was then heated to 400 °C in a N2 atmosphere and kept warm for 2 h. The obtained iron sulfide was recorded as FeS2-S.

[0093] The Fe mentioned in the following analysis example x Cu (1-x) SA, Fe x Cu (1-x) SB, Fe 0.95 Cu 0.05 SA, Fe 0.95 Cu 0.05 SB, Fe 0.9 Cu 0.1 SA or Fe 0.9 Cu 0.1 SB, Fe 0.85 Cu 0.15 SA, Fe 0.85 Cu 0.15 SB was prepared from Example 1. The Fe x Cu (1-x) SS, Fe 0.95 Cu 0.05 SS, Fe 0.9 Cu 0.1 SS, Fe0.85 Cu 0.15 SS was prepared from Example 2. The Fe x Mo (1-x) SA, Fe x Mo (1-x) SB, Fe 0.9 Mo 0.1 SA, Fe 0.9 Mo 0.1 SB was prepared from Comparative Example 1. The Fe x Mo (1-x) SS, Fe 0.9 Mo 0.1 SS was prepared by Comparative Example 2, FeS2-A and FeS2-B mentioned in the following analysis example were prepared by Comparative Example 3, and FeS2-S mentioned in the following analysis example was prepared by Comparative Example 4.

[0094] Analysis Example 1 Analysis of the effect of copper / molybdenum doping on the structure of iron sulfide

[0095] The effects of copper / molybdenum doping on the morphology and structure of iron sulfide were analyzed by SEM. Figure 1 As shown, the ordinary iron sulfide (FeS2-S) prepared in Comparative Example 4 of the present invention and the molybdenum / copper doped iron sulfide (FeS2-S prepared in Comparative Example 2) 0.9 Mo 0.1 SS and Fe prepared in Example 2 0.9 Cu 0.1 The morphology of the iron sulfide (SS) is irregular agglomerates formed by the aggregation of small particles, and the size of the agglomerates is about 4-6μm, indicating that copper and molybdenum doping will not change the macroscopic morphology of iron sulfide. The energy spectrum shows that the Fe and S elements are evenly distributed on the surface of the particles, and evenly distributed copper or molybdenum can be seen, indicating that molybdenum / copper is evenly dispersed into the iron sulfide. The BET specific surface area of ​​iron sulfide, copper-doped iron sulfide and molybdenum-doped iron sulfide is the same, all 3m 2 ·g -1 , indicating that metal cation doping has no significant effect on the specific surface area of ​​iron sulfide.

[0096] The phase structures of iron sulfide, copper-doped iron sulfide and molybdenum-doped iron sulfide were analyzed by XRD. Figure 2 (a) The characteristic diffraction peaks of the XRD diffraction pattern of FeS2-S at 2θ=28.5, 33.0, 37.1, 40.8, 47.4 and 56.3° correspond to the (111), (200), (210), (211), (220) and (311) crystal planes of pyrite-type FeS2 (JCPDS PDF 42-1340), respectively. After metal cation (Cu / Mo) doping, Fe 0.9 Cu0.1 SS and Fe 0.9 Mo 0.1 The diffraction peak of SS also highly matches the characteristic peak of pyrite, and no obvious impurity peaks are observed in the XRD spectra of the three iron sulfides, indicating that metal cation doping does not affect the phase structure of iron sulfide. Figure 2 As shown in (b), the copper-doped iron sulfide prepared with different copper ion addition amounts also has an XRD diffraction peak pattern matching that of pyrite-type FeS2 (JCPDS PDF 42-1340), indicating that the physical structure of the copper-doped iron sulfide studied in the present invention is all pyrite-type FeS2.

[0097] Combined with SEM, it can be seen that Cu and Mo ions are doped into the FeS2 crystals without significantly affecting the overall structure of the crystals.

[0098] Raman spectroscopy was used to analyze the effect of copper doping on the structural characteristics of iron sulfide, such as Figure 3 As shown. Undoped FeS2-S is at 320-420cm -1 There are two obvious vibration peaks in the range, located at 343cm -1 The peak at corresponds to the E g Vibration mode, located at 379cm -1 The peak at corresponds to the A g Vibration mode. After the introduction of copper, Fe 0.9 Cu 0.1 No new characteristic peak appeared in SS, located at 343cm -1 and 379cm -1 The two characteristic peaks at did not undergo obvious displacement or broadening, and the corresponding peak intensity ratios were relatively close, further indicating that copper doping did not change the structure of iron sulfide.

[0099] XPS was used to analyze the effect of copper and molybdenum doping on the valence distribution of elements on the surface of iron sulfide. Figure 4 As shown in (a), the peaks at 707.2 and 708.1 eV in the Fe 2p spectrum of FeS2-S correspond to the Fe 2+ Fe 2p 3 / 2 orbitals, the two peaks at 708.3 and 710.6 eV correspond to Fe 3+ Fe 2p 3 / 2 orbitals, the peak at 713.1 eV corresponds to the satellite peak, and the other five peaks correspond to the Fe 2p 1 / 2 Track. After doping with molybdenum and copper, Fe 0.9 Mo 0.1 SS and Fe 0.9 Cu 0.1 The peak position of the Fe 2p spectrum of SS did not change significantly. Figure 4 As shown in (b), there are three peaks in the S2p of FeS2-S. The peak at 161.7 eV corresponds to S 2- , the peaks at 162.7 and 163.8 eV correspond to S2 2-12 .like Figure 4 As shown in (c), Fe 0.9 Mo 0.1 The peaks at 225.7 and 226.9 eV in the Mo 3d spectrum of SS correspond to S 2- 2s and S2 2- 2s, the peaks at 228.7 and 232.7 eV correspond to Mo 4+ Mo3d 5 / 2 and Mo 3d 3 / 2 orbit, indicating that the introduced molybdenum is mainly in the form of Mo 4+ Exist in the form of. Figure 4 As shown in (d), Fe 0.9 Cu 0.1 The peaks at 932.6 and 952.4 eV in the Cu 2p spectrum of SS correspond to Cu + 2p 3 / 2 and Cu + 2p 1 / 2 orbitals, the peaks at 933.9 and 955.1 eV correspond to Cu 2+ 2p 3 / 2 and Cu 2+ 2p 1 / 2 track.

[0100] The valence distribution of each element changed significantly before and after copper doping, as shown in Table 1. 2- The proportion is as high as 33.87%. 2- The ratio is greatly reduced, Fe 0.9 Mo 0.1 SS and Fe 0.9 Cu 0.1 SS dropped to 10.08% and 8.36% respectively, while S2 2- It increased significantly from 65.73% to 89.97% and 91.69%, indicating that metal cation doping can produce more S2 on the surface of iron sulfide. 2- , this part S2 2- Obviously, it is formed by the coordination of S with Cu and Mo. 3+ From 28.44% to 26.75% and 26.71% respectively. 0.9 Cu 0.1 High-valent Cu was introduced on the SS surface 2+ , accounting for 26.61% 15 .

[0101] Table 1 Surface chemical composition before and after iron sulfide doping

[0102]

[0103] Analysis Example 2 Effect of sulfur source on mercury removal performance in copper / molybdenum doped iron sulfide

[0104] At 50℃, 6% SO2+6% O2 atmosphere, Hg 0 Concentration 150 μg·m -3 The mercury removal test was carried out for 60 minutes under the conditions of , and the amount of adsorbent was 10mg. Figure 5 (a)~ Figure 5 As shown in (c), the demercuration performance of molybdenum-doped iron sulfide is poor. 0.9 Mo 0.1 Hg of SA-180 at 60min 0 The adsorption efficiency is only 32%, indicating that molybdenum doping actually inhibits the mercury removal performance of iron sulfide.

[0105] Thiourea as sulfur source, Hg from iron sulfide 0 The adsorption performance was relatively less affected by the sulfidation temperature. FeS2-A-160 with a sulfidation temperature of 160 °C showed the best mercury removal performance, but its Hg 0 The adsorption efficiency is only 63.5%.

[0106] The mercury removal performance of copper-doped iron sulfide is greatly affected by the sulfidation temperature. The higher the sulfidation temperature, the worse the mercury removal performance of the adsorbent. 0.9 Cu 0.1 SA-120 showed the best mercury removal performance, with Hg 0 The adsorption efficiency is still 92%, indicating that copper doping can improve the mercury removal performance of iron sulfide. The optimal sulfidation temperature of copper-doped iron sulfide with thiourea as the sulfur source is 120-140°C.

[0107] The effect of sodium sulfide as a sulfur source on mercury removal performance, such as Figure 5 (d) The copper-doped iron sulfide prepared by using sodium sulfide as the sulfur source has different trends in mercury removal performance. The copper-doped iron sulfide synthesized by sulfurization at 160℃ shows the best mercury removal performance, with Hg 0 The adsorption efficiency is still 96%, indicating that sodium sulfide is more suitable as a sulfur source for hydrothermal sulfidation than thiourea, and the optimal sulfidation temperature of copper-doped iron sulfide with sodium sulfide as the sulfur source is 160-180°C.

[0108] Analysis Example 3 Effect of Preparation Method on Mercury Removal Performance in Copper / Molybdenum Doped Iron Sulfide

[0109] The effect of dry sulfidation on the mercury removal performance of iron sulfide was studied. Figure 6 The three iron sulfides synthesized by dry sulfur sulfidation have better mercury removal performance than wet sulfidation, and copper-doped iron sulfide shows the best mercury removal performance, with Hg 0 The adsorption efficiency remained at 98%, and was still 95% at 120 min.

[0110] The demercuration performance of molybdenum-doped iron sulfide is slightly weaker, and the Hg 0 The adsorption efficiency is 91%.

[0111] This shows that the sulfidation method is an important factor affecting the mercury removal performance of iron sulfide. Compared with wet sulfidation, the adsorbent obtained by dry sulfidation of elemental sulfur has better mercury removal performance. Molybdenum / copper doping can further improve the mercury removal efficiency of iron sulfide, and the improvement effect of copper doping is more significant.

[0112] Analysis Example 4 Effect of Copper Doping Amount on Copper-doped Iron Sulfide

[0113] like Figure 7 As shown in the figure, the mercury removal performance of copper-doped iron sulfide increases first and then decreases with the amount of copper added. The Hg 0 The adsorption efficiency is 80%. After the introduction of copper, Fe 0.95 Cu 0.05 The efficiency of SS is increased to 90%. After increasing the copper doping amount, Fe 0.9 Cu 0.1 SS achieves the highest mercury removal efficiency of 98%. However, if the copper doping level is increased, Fe 0.85 Cu 0.15 SS Hg 0 The adsorption efficiency dropped to 85%. In addition, the efficiency of copper sulfide is only 81%, and the chemical formula of copper-doped iron sulfide is Fe 0.9 Cu 0.1 SS, that is, when the molar ratio of copper and iron elements is 0.9:1, the mercury adsorption performance is optimal.

[0114] Analysis Example 5 Effect of Flue Gas Composition and Temperature

[0115] There are many components in non-ferrous smelting flue gas, such as O2, SO2, HCl, H2O, etc. The flue gas temperature may also affect the demercuration performance of copper-doped iron sulfide. Figure 8 As shown in (a), Fe 0.9 Cu 0.1 SS Hg 0 Adsorption performance, and Figure 8 The mercury concentration in all atmosphere conditions is 150 μg.m -3It can be seen that 6% SO2 and 5ppm HCl both promote the removal of mercury from copper-doped iron sulfide. The average Hg 0 The adsorption efficiency increased from 85% to 97% and 98% respectively; 6% O2 and 10% H2O had no obvious effect on the mercury removal performance of the adsorbent, indicating that copper-doped iron sulfide has good resistance to flue gas poisoning.

[0116] Subsequently, mercury removal tests were carried out under simulated smelting flue gas (SFG: 6% SO2+6% O2+5ppm HCl+10% H2O) conditions. 0 The adsorption efficiency is as high as 100%, indicating that Fe 0.85 Cu 0.15 SS can maintain good mercury removal performance in complex smelting flue gas environment. Figure 8 As shown in (b), the effect of mercury-containing flue gas on the adsorption performance of copper-doped iron sulfide was investigated. It can be seen that Fe 0.9 Cu 0.1 SS has good mercury removal performance at both 25℃ and 50℃. However, the mercury removal performance gradually decreases with the increase of temperature. At 100℃, after 120min of mercury removal test, the mercury removal efficiency drops to 67%. This is due to the high mercury removal performance of Fe 0.9 Cu 0.1 This is due to the weak mercury adsorption capacity of some active sites on the SS surface.

[0117] Analysis Example 6 Mercury Adsorption Capacity Test

[0118] Mercury adsorption capacity is an important indicator for evaluating the mercury removal performance of adsorbents. 0 The adsorption capacity of 6% O2+6% SO2 at 50℃ and gas flow rate of 600mL·min -1 , Hg 0 Concentration 150 μg.m -3 Under the conditions, the FeS2-S prepared in Comparative Example 4 and the FeS2-S prepared in Example 2 were respectively 0.9 Cu 0.1 SS for long-term Hg 0 Adsorption test, the results are as follows Fig. 9 As shown: FeS2-S reached 90% penetration at 45h, and Hg was calculated by integration 0 The adsorption capacity is 8.3 mg g -1 In comparison, Fe 0.9 Cu 0.1 SS reached 90% penetration only after 120h, and the effective adsorption time was 2.7 times longer than that of FeS2-S. 0 The adsorption capacity is 25.0 mg g -1 , which is 3 times that of FeS2-S.

[0119] The pseudo-first-order kinetic model and pseudo-second-order kinetic model were used to further analyze the relationship between FeS2-S and Fe 0.9 Cu 0.1 SS Hg 0 The adsorption characteristics and their adsorption kinetic behaviors were studied as shown in Eqs. 1, 2 and 3.

[0120] Pseudo-first-order kinetic model:

[0121]

[0122] Pseudo-second-order kinetic model:

[0123]

[0124] or

[0125] In the formula, q t and q e are the mercury adsorption capacity at time t (min) and adsorption equilibrium, respectively. k1 (min -1 ) and k2(g·mg -1 ·min -1 ) represent the reaction rate constants of the two kinetic models.

[0126] like Fig.10 As shown in Table 2, the pseudo-first-order kinetic model is effective for FeS2-S and Fe 0.9 Cu 0.1 The fitting degree of SS mercury capture adsorption curve (R 2 ) were 0.8694 and 0.7754 respectively. The fitting degree of the pseudo-second-order kinetic model was improved to 0.9284 and 0.9404 respectively, indicating that FeS2-S and Fe 0.9 Cu 0.1 SS vs Hg 0 The adsorption characteristics of Hg 0 The chemical adsorption of FeS2 and Fe 0.9 Cu 0.1 S adsorbs Hg 0 The kinetic parameters of the two were obtained under the pseudo-second-order kinetic model. e ) were 9.1 and 27.5 mg·g -1 , which is closer to the experimental data. Kinetic studies have shown that FeS2 and Fe 0.9 Cu 0.1 SS vs Hg 0 The adsorption of Hg mainly depends on the active sites on the surface of iron sulfide. 0 of chemical adsorption.

[0127] Table 2 Model parameters of pseudo-first-order kinetics and pseudo-second-order kinetics

[0128]

[0129] The mercury adsorption performance of copper-doped iron sulfide was compared with that of other typical metal sulfides, as shown in Table 3. Copper-doped iron sulfide showed better Hg 0 Its mercury adsorption capacity is significantly higher than that of other metal sulfides, and is higher than that of ordinary iron disulfide (2.7 mg·g -1 ) and can maintain high mercury removal performance in 6% SO2+6% O2 atmosphere, which is suitable for high SO2 smelting flue gas mercury removal. 0.9 Cu 0.1 SS Hg removal 0 The cost is 471.00 yuan / (kg Hg 0 ) (considering only the raw material cost of adsorbent preparation), it is only 2 / 5 of ordinary iron disulfide and 1 / 250 of carbon-based adsorbent. Therefore, copper doping achieves an increase in the adsorption capacity of iron sulfide mercury, while at the same time 0 It has significant economic advantages in removal and has good application potential.

[0130] Table 3 Adsorption capacity of different sulfide adsorbents

[0131]

[0132]

[0133] Analysis Example 7: Study on the Mercury Adsorption Mechanism of Copper-doped Iron Sulfide

[0134] By XPS, Hg 0 Fe before and after adsorption 0.9 Cu 0.1 SS surface element valence changes, such as Fig.11 As shown in Table 4, it can be seen that copper-doped iron sulfide (Fe 0.9 Cu 0.1 Cu in SS 2+ , Fe 3+- The main Hg 0 Adsorption active sites can directly transfer Hg 0 Oxidized to Hg 2+ .

[0135] Fig.11 (a) shows the Fe 2p XPS spectrum of the adsorbent. The spectrum can be decomposed into eight peaks. The two peaks at 707.2 and 708.1 eV correspond to Fe 2+ Fe 2p 3 / 2orbitals, the two peaks at 708.3 and 710.6 eV correspond to Fe 3 + Fe 2p 3 / 2 orbital, the peak at 713.1 eV corresponds to the satellite peak of Fe2p 3 / 2 orbitals, and the other five peaks correspond to Fe2p 1 / 2 Orbital. Adsorption of Hg 0 After that, Fe 2+ and Fe 3+ The peak position of Fe 3+ The proportion of Fe 2+ The increase in the ratio of Fe 3+ It is Hg 0 oxidation active sites.

[0136] like Fig.11 As shown in (b), the S2p XPS spectrum of the adsorbent contains three peaks. The peak at 161.9 eV corresponds to S 2- , the peaks at 162.7 and 163.9 correspond to S2 2- . Adsorption of Hg 0 After S2 2- and S 2- The ratio of S2 2- Not Hg 0 oxidation active sites.

[0137] like Fig.11 As shown in (c), the Cu 2p XPS spectrum of the adsorbent contains four peaks. The peaks at 932.6 and 952.4 eV correspond to Cu + , the peaks at 933.9 and 955.1 eV correspond to Cu 2+ . Adsorption of Hg 0 After that, Cu 2+ The proportion of Cu + The increase in the ratio of Cu 2+ Also Hg 0 oxidation active sites.

[0138] like Fig.11 As shown in (d), the Hg 4f XPS spectrum contains two peaks, the peaks at 104.7 eV and 100.8 eV correspond to Hg 2+ Hg 4f 5 / 2 and Hg 4f 7 / 2 orbital, indicating that in Fe 0.9 Cu 0.1 S adsorbs Hg via chemical oxidation 0 , which is consistent with the results of adsorption kinetics analysis.

[0139] Table 4Fe 0.9 Cu 0.1 Surface chemical composition before and after SS adsorption

[0140]

[0141] Analysis Example 8: Investigation of the Mercury Adsorption Mechanism of Copper-doped Iron Sulfide

[0142] The mercury adsorption on the Fe prepared in Example 2 was analyzed by mercury temperature programmed desorption (Hg-TPD). 0.9 Cu 0.1 The morphology of SS surface, such as Fig.12 As shown in the figure, the Hg-TPD curve has an obvious mercury desorption peak at 270℃, indicating that Hg 0 HgS was formed on the adsorbent surface after oxidative adsorption.

[0143] Combining material characterization and theoretical calculation, it is known that S2 2- , Fe 3+ and Cu 2+ It is the active component for mercury removal in copper-doped iron sulfide. Cu forms copper doping by replacing Fe or S. Copper doping promotes the synergistic effect between the Fe and Cu sites of iron sulfide and Hg atoms, and the adsorption energy increases from -55.85 kJ·mol -1 Increased to -68.70 kJ·mol -1 In addition, the pre-adsorbed Cu sites alone or in cooperation with Fe sites further increased the adsorption energy of Hg to -80.89 and -96.52 kJ·mol -1 .

[0144] It can be inferred that Hg 0 In Fe 0.9 Cu 0.1 There are two ways of adsorption on SS. The first way is Hg 0 With metal site Cu 2+ -Fe 3+ The reaction forms [Fe-Hg-Cu] and finally generates HgS. The reaction is as follows:

[0145] Hg 0 +Cu 2+ -Fe 3+ -S→[Fe·Hg·Cu]-S

[0146] [Fe·Hg·Cu]-S→[Cu + ]+Fe 2+ +HgS

[0147] The second pathway is Hg 0 Directly bind to the metal site Fe 3+Reaction to form [Fe-Hg], the reaction is as follows:

[0148] Hg 0 +Fe 3+ -S→[Fe·Hg]-S

[0149] [Fe·Hg]-S→[Fe 2+ ]+HgS

[0150] In both pathways, Hg 0 They will chemically adsorb on the surface of copper-doped iron sulfide to form stable HgS.

[0151] The present invention synthesizes a variety of iron sulfides through a molybdenum / copper doping strategy. 0.9 Cu 0.1 Hg removal of SS 0 The performance is excellent. The effect of cation doping on the surface chemical properties of iron sulfide is studied, and the strengthening mechanism of the active sites for mercury removal on the surface of iron sulfide is clarified, thereby significantly improving the mercury adsorption capacity of iron sulfide. The main conclusions are as follows:

[0152] (1) The doping of copper / molybdenum did not change the original pyrite (FeS2) phase structure and specific surface area of ​​iron sulfide, but the surface chemical properties were regulated by element doping. Hydrothermal and elemental sulfur sulfidation can increase the proportion of unsaturated sulfur on the surface of doped iron sulfide. The doping of sulfur-philic metal cations copper / molybdenum can increase the S2 2- The proportion increased from 65.73% to 91.69% and 89.97% respectively, Fe 3+ The ratio dropped from 28.44% to 26.75% and 26.71% respectively. 4+ , copper doping introduces the active component high-valent Cu 2+ .

[0153] (2) Hg in iron sulfide before and after doping 0 Adsorption experiments have shown that copper-doped iron sulfide has better mercury removal performance than iron sulfide, molybdenum-doped iron sulfide and copper sulfide. In a simulated smelting flue gas atmosphere (6% SO2+6% O2+5ppm HCl+10% H2O), its mercury removal efficiency is close to 100%. The suitable operating temperature of copper-doped iron sulfide is 50°C or below, and it is suitable for smelting flue gas after washing or condensation. In a 6% SO2+6% O2 atmosphere, copper-doped iron sulfide has a good mercury removal performance against Hg 0 The adsorption capacity is up to 25.0 mg·g -1 , which is 3 times that of undoped iron sulfide and 9 times that of ordinary iron disulfide. 0 The cost is only 471.00 yuan / (kg Hg 0), which is less than 1 / 250 of that of industrial carbon-based adsorbents, and has obvious economic advantages. Adsorption kinetics analysis shows that chemical adsorption is the main rate-controlling step in the mercury removal process.

[0154] (3)Fe 3+ , Cu 2+ and S2 2- are the active sites for mercury removal in copper-doped iron sulfide, and they participate in Hg 0 DFT calculations show that copper doping reduces the energy gap of FeS2 from 0.647 eV to 0.10 eV, and the d-band center shifts negatively, promoting the oxidation of Hg 0 Adsorption and electron transfer; Compared with the single Fe site and Cu site, the charge density of the Fe-Hg bond and Cu-Hg bond regions increases, which strengthens the charge transfer of Hg atoms and enhances the interaction between Hg and the Fe and Cu sites of copper-doped iron sulfide. The d orbitals of the Fe and Cu sites overlap with the s orbitals of Hg, exerting a synergistic demercuration effect, and the adsorption energy increases from -55.85 kJ·mol -1 (Fe site) and -39.61 kJ·mol -1 (Cu site) increased to -68.70 kJ·mol -1 In addition, the pre-adsorbed Cu sites on the FeS2(100) surface cooperate with the Fe sites to 0 The adsorption energy is -96.52 kJ·mol -1 , Cu site to Hg 0 The adsorption energy is -80.89 kJ·mol -1 .

[0155] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing copper-doped iron sulfide, characterized in that: Includes steps: S1. preparing a metal salt solution from ferric nitrate and copper nitrate; wherein the sum of the molar concentrations of iron ions and copper ions in the metal salt solution is 0.003 to 0.06 mol / 25 ml; S2. dissolving a sulfur source in a metal salt solution to obtain a mixed solution, heating the mixed solution to 120-180° C. under high pressure for 12 hours, and separating the solid matter therein to obtain copper-doped iron sulfide; the molar concentration of the sulfur source in the mixed solution is 0.01-0.1 mol / 50 ml; Alternatively, the metal salt solution is heated to 120-180° C. under high pressure and kept warm for 12 hours to obtain a precursor, and the precursor is mixed with elemental sulfur and heated to 400° C. and kept warm for 2 hours to obtain copper-doped iron sulfide.

2. The preparation method according to claim 1, characterized in that: The sulfur source includes thiourea and sodium sulfide.

3. The preparation method according to claim 2, characterized in that: When the sulfur source is thiourea, heating the mixed solution to 120-180° C. under high pressure and keeping the temperature for 12 hours includes: heating the mixed solution to 120-140° C. under high pressure and keeping the temperature for 12 hours.

4. The preparation method according to claim 3, characterized in that: When the sulfur source is sodium sulfide, heating the mixed solution to 120-180° C. under high pressure and keeping the temperature for 12 hours includes: heating the mixed solution to 160-180° C. under high pressure and keeping the temperature for 12 hours.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the precursor to the elemental sulfur is 1:1-2.

6. The preparation method according to claim 1, characterized in that: In the copper-doped iron sulfide, the molar ratio of iron ions to copper ions is 0.9-0.95:0.05-0.

1.

7. A copper-doped iron sulfide, characterized in that: The copper-doped iron sulfide is prepared by the method for preparing the copper-doped iron sulfide according to any one of claims 1 to 6.

8. Use of the copper-doped iron sulfide in flue gas mercury removal as claimed in claim 7, characterized in that: The method comprises the steps of: introducing mercury-containing flue gas into the copper-doped iron sulfide to carry out a demercuration reaction, wherein the reaction temperature of the demercuration reaction is 25° C. to 50° C., and the flow rate of the mercury-containing flue gas is 600 mL·min. -1 , the mercury-containing flue gas contains Hg 0 Concentration 100~200μg.m -3 .

9. The use according to claim 8, characterized in that: The mercury-containing flue gas includes sulfur-containing flue gas, in which the volume fraction of sulfur dioxide is 4-8%, and the volume fraction of oxygen is 4-8%.

10. The use according to claim 9, characterized in that: The concentration of HCl in the mercury-containing flue gas is 2-6 ppm.

Citation Information

Patent Citations

  • Cysteine-based antibacterial nano iron sulfide mixture, and preparation method and application thereof

    CN109260222A

  • Iron-doped copper sulfide nanosheet material with rich defects and preparation method and application thereof

    CN109354056A

  • Preparation method of sulfide phase nano material

    CN115571912A

  • Preparation and regeneration method of bimetallic Fe-Cu-BTC desulfurizer

    CN116173924A

  • Copper-doped Zn0. 5Cd0. 5S composite visible-light-driven photocatalyst as well as preparation method and application thereof

    CN117324008A

Cited By

  • Single-phase Fe0. 8Cu0. 2S2 material as well as solid-phase sintering preparation method and application thereof

    CN121948550A